The Effectiveness of Oromotor Massage Stimulation on the Development of Language and Speech Skills in Babies Aged 12-18 Months - Siregar, Debi Novita; Laoli, Nofika Kristiani; Pasaribu, Debora Afriyani br.; Silangit, Nikita Novelia (Indonesian Journal of Global Health Research, 2024)
Development is an increase in abilities or skills in more complex body structures and functions gradually and regularly. One component of child development is language. The development of language and speech abilities in children involves cognitive, sensori motor, psychological, emotional and environmental development. Talking is when someone makes a sound with the aim of conveying something to another person. Children need to learn several skills to be able to speak correctly. The aim of this research is to determine the effectiveness of oromotor massage stimulation on the development of language and speech abilities of babies aged 12-18 months at Lutuna Baby SPA. The method in this research is the approach used is one group pre test-post test design, the type of quantitative research with the research design is Praexperimental. The population in this study were all mothers who had babies aged 12-18 months and were willing to do oromotor massage, totaling 30 people. This research uses a measuring instrument, namely an observation sheet. The results of the study showed that the average difference in pretest-posttest babies' speech and language abilities was 0.933 and the p value was 0.000. This proves the influence of oromotor massage stimulation on improving the speech and language abilities of babies aged 12-18 months.